Assessing the phytoremediation potential of crop and grass plants for atrazine-spiked soils. (October 2017) - Sánchez, Virtudes; López-Bellido, Francisco Javier; Cañizares, Pablo; Rodríguez, Luis
Abstract: Pollution of soil and groundwater by atrazine has become an increasing environmental concern in the last decade. A phytoremediation test using plastic pots was conducted in order to assess the ability of several crops and grasses to remove atrazine from a soil of low permeability spiked with this herbicide. Four plant species were assessed for their ability to degrade or accumulate atrazine from soils: two grasses, i.e., ryegrass ( Lolium perenne ) and tall fescue ( Festuca arundinacea ), and two crops, i.e., barley ( Hordeum vulgare ) and maize ( Zea mays ). Three different doses of atrazine were used for the contamination of the pots: 2, 5 and 10 mg kg −1 . 16 days after spiking, the initial amount of atrazine was reduced by 88.6–99.6% in planted pots, while a decrease of only 63.1–78.2% was found for the unplanted pots, thus showing the contribution of plants to soil decontamination. All the plant species were capable of accumulating atrazine and its N-dealkylated metabolites, i.e., deethylatrazine and deisopropylatrazine, in their tissues. Some toxic responses, such as biomass decreases and/or chlorosis, were observed in plants to a greater or lesser extent for initial soil doses of atrazine above 2 mg kg −1 . Maize was the plant species with the highest ability to accumulate atrazine derivatives, reaching up to 38.4% of the initial atrazine added to the soil. Rhizosphere degradation/mineralization by microorganisms or plant enzymes, together with degradation inside the plants, have been proposed as the mechanisms that contributed to a higher extent than plant accumulation to explain the removal of atrazine from soils. Graphical abstract: Highlights: The presence of plants increased atrazine removal up to 36% with respect to unplanted pots. Plants were capable of accumulating atrazine and its N-dealkylated metabolites in their tissues. Maize was the plant species with the highest ability to accumulate atrazine derivatives. Atrazine was mainly removed by biochemical degradation in the rhizosphere.